Levatiracetam for the management of Lance-Adams syndrome - ILIK*, Faik; ILIK, Mustafa Kemal; Ã‡OVEN, Ä°lker (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Ilik F, Ilik MK, Çöven I. Levatiracetam for the management of Lance-Adams syndrome. Iran J Child Neurol. 2014 Spring 8(2):57-59. Chronic post-hypoxic myoclonus, also known as Lance-Adams syndrome (LAS) is a neurological complication characterized by uncontrolled myoclonic jerks following cardiac arrest. In this article, clinical manifestation and symptomatic treatment options are discussed especially concerning the rationale of use of levatiracetam in patients with Lance-Adams syndrome. Clinical presentation is action myoclonus associated with cerebellar ataxia, postural imbalance, and very mild intellectual deficit. An 18-year-old female patient was admitted to our intensive care unit in a coma. She had a cardiorespiratory arrest after a splenectomy in a local hospital. Then, myoclonic movements were continuously observed over the entire body, including the face. On day 14 of hospitalization, we started levatiracetam 1000 mg daily. The frequency of convulsion movements was reduced. The patient level of consciousness was 15 on the Glasgow coma scale (GCS) on the Mini-Mental State Examination (MMSE) score was 23 out of 30. She was later transferred to the rehabilitation department. Vigilance is required to ensure early diagnosis and timely intervention for the myoclonic jerks. In conclusion, we would like to emphasize that LAS should be considered in patients with the myoclonic jerks following cardiac arrest and that levatiracetam therapy may be useful as treatment. References 1. Lance JW, Adams RD. The syndrome of intention or action myoclonus as a sequel to hypoxic encephalopathy. Brain 1963; 86: 111-136. 2. Guo XH, Yu SY, Liu J, Wu WP, Pu CQ, Zhu K. Posthypoxic myoclonus treated with 5-hydroxytryptophan: a case report. J Clin Neurol 2002; 15: 313-6. 3. Arpesella R, Dallocchio C, Arbasino C, Imberti R, Martinotti R, Frucht SJ. A patient with intractable posthypoxic myoclonus (Lance-Adams syndrome) treated with sodium oxybate. Anaesth Intensive Care 2009; 37:314-8. 4. Werhahn KJ, Brown P, Rompson PD, Marsden CD. The clinical features and prognosis of chronic post-hypoxic myoclonus. Mov Disord 1997; 12: 216-20. 5. Frucht SJ, Trost M, Ma Y, Eidelberg D. The metabolic topography of post-hypoxic myoclonus. Neurology 2004; 62: 1879-1881. 6. Frucht S, Fahn S. The clinical spectrum of post-hypoxic myoclonus. Mov Disord 2000; 15 (Suppl 1): 2-7. 7. Matsumoto RR, Truong DD, Nguyen KD, Dang AT, Hoang TT, Vo PQ, Sandroni P. Involvement of GABA(A) receptors in myoclonus. Mov Disord 2000; 15(Suppl1):47-52.